East China Sea Storm Surge Modeling and Visualization System: The Typhoon Soulik Case - Zengan Deng; Feng Zhang; Linchong Kang; Xiaoyi Jiang; Jiye Jin; Wei Wang (The Scientific World Journal)
East China Sea (ECS) Storm Surge Modeling System (ESSMS) is developed based on Regional Ocean Modeling System (ROMS). Case simulation is performed on the Typhoon Soulik, which landed on the coastal region of Fujian Province, China, at 6 pm of July 13, 2013. Modeling results show that the maximum tide level happened at 6 pm, which was also the landing time of Soulik. This accordance may lead to significant storm surge and water level rise in the coastal region. The water level variation induced by high winds of Soulik ranges from −0.1 to 0.15 m. Water level generally increases near the landing place, in particular on the left hand side of the typhoon track. It is calculated that 0.15 m water level rise in this region can cause a submerge increase of ~0.2 km2, which could be catastrophic to the coastal environment and the living. Additionally, a Globe Visualization System (GVS) is realized on the basis of World Wind to better provide users with the typhoon/storm surge information. The main functions of GVS include data indexing, browsing, analyzing, and visualization. GVS is capable of facilitating the precaution and mitigation of typhoon/storm surge in ESC in combination with ESSMS.